A new species of the endemic genus Hemicyrthus Reiche (Coleoptera: Scarabaeidae: Dynastinae) from New Caledonia, with a revised key - Krell, Frank-Thorsten; Theuerkauf, Jörn (Zootaxa, 2015)
Hemicyrthus blaffarti new species (Coleoptera: Scarabaeidae: Dynastinae) from the Parc Provincial de la Rivière Bleue in southern New Caledonia is described. It differs from the most similar species, H. elongatus, by the completely and sharply margined pronotal base, the presence of elytral micropunctures, shorter apical setae of the mesotibiae and meta-tibiae, and a different shape of the parameres. For the first time, a sexually dimorphic character is described in this genus: the median emargination of the last sternite has a developed margin in males, but not in females. A revised key for all Hemicyrthus species is given. Hemicyrthus as a genus of short-range endemics, and its biogeographical relationships are briefly discussed.